Counseling for Children with Special Needs - Mutiara Tanila; Amirah Diniaty (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to examine the role of counseling services in supporting psychosocial development and social adaptation among children with special needs. The research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews with counselors, parents, and teachers, and documentation review. Data analysis followed the interactive model of Matthew B. Miles, A. Michael Huberman, and Johnny Saldaña. The findings indicate that counseling significantly contributes to emotional regulation, social skill development, and adaptive behavior improvement among children with special needs. Counseling functions not only as a therapeutic intervention but also as a preventive and developmental approach. Furthermore, collaboration between counselors, families, and schools enhances intervention effectiveness. This study highlights counseling as a psychosocial support system that strengthens independence, social integration, and overall well-being of children with special needs.